PERAN WISATA ALAM CIKOROMOY DALAM MENINGKATKAN EKONOMI MASYARAKAT DI KABUPATEN PANDEGLANG - Kameliya Artamevira; Shabila Anjani; Mamas Supartini; Ade Fauji (Yayasan Education and Social Center, 2026)
Cikoromoy Natural Tourism has significant potential as a local economic driver through the development of community-based tourism activities. This community service activity aims to improve the capacity of local communities in utilizing tourism potential to strengthen economic opportunities around the Cikoromoy Tourism Area, Mandalawangi District, Pandeglang Regency. The activity was carried out in January 2026 through several stages, including field observation, socialization, business assistance, digital marketing education, and evaluation. The participants involved local communities, micro, small, and medium enterprises (MSMEs), food vendors, parking service providers, and other tourism-related business actors. The results of the activity showed that Cikoromoy Natural Tourism has contributed to increasing community economic activities through the growth of various tourism-supporting businesses. The assistance program improved community understanding of business management, product innovation, service quality improvement, and the utilization of digital media for promotion. Furthermore, the activity encouraged greater community participation in maintaining tourism sustainability and strengthening cooperation among local business actors. The implementation of this program demonstrates that tourism development based on local potential can become an effective strategy to increase community income and support sustainable economic growth. Continuous assistance and collaboration between communities, tourism managers, and local government are needed to optimize the economic benefits of Cikoromoy Natural Tourism.